PENGARUH DARI MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN APLIKASI PERANGKAT LUNAK DAN PERANCANGAN INTERIOR GEDUNG - Daffa Rizqi Ramadhan; Tuti Iriani (Jurnal Pendidikan Teknik Bangunan, 2022)
This study aims to show the effect that the flipped classroom has as a learning model on the learning outcomes of class XII students in the subject of Software Applications and Building Interior Design in competency skills of Modeling Design and Building Information at SMK Negeri 52 Jakarta.The method used is a quasi-experimental research design using a randomized pretest and posttest control group design. The sample used in this study amounted to 54 students. The treatment in the form of a flipped classroom learning model was tested on the experimental class, and the lecture method was applied to the control class.The results of this study indicate that the class that has been applied to the flipped classroom learning model experiment is higher than the control class, this can be seen from the results of the two-class post-test where the experimental class got a score of 86,92 and the control class got a score of 80,61. The difference in learning outcomes can be seen from the average of the two classes and is evidenced from the results of the regression test which explains that the application of the class with the flipped classroom learning model can affect learning outcomes. This is evidenced by the results of significance 0.05 with the results of the application of the flipped classroom having an effect. The amount of R square or the percentage ratio of how much influence the application of this learning model has is 10.3%